The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/cc.36819875707
|View full text |Cite
|
Sign up to set email alerts
|

Learning disabilities and the developmental education program

Abstract: Community colleges face a new challenge: to provide appropriate instruction and services to learning‐disabled students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Although the literature states that two-year colleges more frequently utilize remediation as an intervention strategy (Almeida, 1991;Young & Staebler, 1987), community college focus group participants did not mention remedial programs or classes in any of their discussions.…”
Section: Implications For Practicementioning
confidence: 95%
See 1 more Smart Citation
“…Although the literature states that two-year colleges more frequently utilize remediation as an intervention strategy (Almeida, 1991;Young & Staebler, 1987), community college focus group participants did not mention remedial programs or classes in any of their discussions.…”
Section: Implications For Practicementioning
confidence: 95%
“…Two-year institutions often provide a wide range of services to address the underprepared learner such as testing and career counseling ; tutoring in basic subjects; adult education and General Education Development (GED) training ; transfer opportunities to four-year institutions; developmental remedial education in reading, math, writing, and vocabulary ; and vocational assessment (Young & Staebler, 1987).…”
mentioning
confidence: 99%
“…The mission of these two-year postsecondary institutions differs when compared to that of four-year institutions, and the differences should affect the types of services offered to students with learning disabilities (Almeida, 1991;Brinckerhoff, Shaw, & McGuire, 1993;Cohen, 1989;Johnson & Walberg, 1989;Mellard, 1994;Nelson & Kraft, 1989;Nelson, Smith, & Dodd, 1991;Young & Staebler, 1987). Almeida (1991) suggested that the community college mission focuses on three areas: (a) the transfer function, (b) job training and retraining, and (c) the education of underprepared students who possess low abilities in reading, math, and other learning skills.…”
mentioning
confidence: 98%
“…Two-year postsecondary institutions provide a wide array of services to meet their mission of addressing the underprepared learner (Nelson & Kraft, 1989). Some of these services include (but are not limited to) testing and career counseling; tutoring in basic subjects; adult education and General Education Development (GED) training; opportunities for transfer to a four-year school; developmental remedial education in reading, math, writing, and vocabulary; and vocational assessment (Young & Staebler, 1987).…”
mentioning
confidence: 99%